Administration and Claims Documentation System for Non Integrated Joint Venture Contract - Muhammad Multazam; Ayomi Dita Rarasati (Journal of International Conference Proceedings (JICP), 2019)
The development of technology in modern times requires contractors especially in Indonesia to compete and adjust their capabilities with foreign contractors whose technology has been developed rapidly. One of the efforts is to establish a joint venture company. Construction project has various risk that influence the relationship between the engaging party and might trigger conflict. In order to avoid it, it is necessary to develop administrative and claim documentation system. A case study is used to obtain this research aim and analyze factors that dominate the project claims. Therefore, unavoidable risk can be managed in this type of contract.